Estimated Prevalence of Caprine Paratuberculosis in Boer Goat Herds in Missouri, USA. (28th November 2012) - Pithua, Patrick; Kollias, Nathaniel S.
Abstract : The objective of this study was to estimate true animal-level and herd-level prevalence of Mycobacterium avium subsp. paratuberculosis (MAP) antibodies in Missouri Boer goat herds. Sera harvested from blood samples collected from goats ≥24 months of age in 25 Missouri Boer goat herds were tested for presence of MAP antibodies using a commercial ELISA kit. Herds were declared positive for MAP if one or more goats in the herd tested positive for MAP antibodies. True animal, within-herd, and between-herd prevalences were calculated using the Rogan-Gladen estimator and were 1.4% (95% CI = 0.1 to 3.6%), 3% (95% CI = 0 to 6%), and 54.7% (95% CI = 28.2 to 86.2%), respectively. Findings in this study confirmed that MAP infection is endemic in Missouri Boer goat herds.